-2/7w+9/10+6w=1663/70

Simple and best practice solution for -2/7w+9/10+6w=1663/70 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2/7w+9/10+6w=1663/70 equation:


w in (-oo:+oo)

(-2/7)*w+6*w+9/10 = 1663/70 // - 1663/70

(-2/7)*w+6*w+9/10-(1663/70) = 0

(-2/7)*w+6*w+9/10-1663/70 = 0

40/7*w-160/7 = 0 // + 160/7

40/7*w = 160/7 // : 40/7

w = 160/7/40/7

w = 4

w = 4

See similar equations:

| 35/3=5/6m+4m+2 | | 1/2d+5/8-2/7d=-73/56 | | -1/3+3/4w-2/5w=-1/3 | | 3+5n-6/7n=-30/77 | | -8+1/2w+w=-83/10 | | (5x+1)2=6 | | 5p^2+3p/3p | | 1/2a+1/2-a=-2 | | 7/9+7w+6/7w=-397/126 | | (4x)/3-(2x+3)/6=9/2 | | -1+2/5n+2/5n=-23/55 | | -5/8-5/7a+2a=25/56 | | 8+5a-7a=100/11 | | -26/5=3k+4/5k-9 | | 7+4/5m+1/2m=153/20 | | -40=2(4-3s) | | 3n+1/3+4n=53/12 | | -52/5=-3t+t-10 | | x+7/9-3/5x=191/315 | | k-3/5+1/3k=-29/15 | | 2b+5+2b=29 | | 9/10+b+2b=-81/10 | | 3(9-2x-9)+4(7x+6)=26 | | 5/7=-a+6/7a+6/7 | | 3/8+4a-1/2a=-277/8 | | 7+2/7a+1/3a=722/105 | | 2x-1+2/3x=-23/15 | | 17=3d-7d+5 | | 20=7w+4w+9 | | -1/5n-3/7-3n=-139/63 | | 1/3+1/2=5 | | 5x+5/12-4x-1/3=11/12 |

Equations solver categories